Oxidative Stress in Critical Conditions and its Correction - N. A. Osipova; N. V. Edeleva; R. I. Yakubovskaya; Ye. R. Nemtsova; V. I. Chissov (Общая реаниматология)
Severe postoperative complications and critical conditions caused by profuse hemorrhage, pulmonary thromboembolism, anaphylactic shock in response to drugs, as well as circulatory arrest, pyoseptic processes are accompanied by significant activation of free radical lipid oxidation along with progressive depletion of the antioxidative defense system, i. e. the development of oxidative stress underlying the development of acute multiple organ dysfunctions (MOD) of posthypoxic or toxemic genesis, and they require special treatment policy. The active antioxidants Ceruloplasmin and Laprot based on natural human protein antioxidants are the drugs of choice in correcting oxidative stress. Their use as part of traditional intensive care restores imbalance of oxidative-antioxidative processes in the body and significantly enhances the efficiency of therapy for critical conditions and it should be regarded as an essential pathogenetic component of complex intensive care. The developed tactics of effective antioxidant therapy promotes optimization of the course of a rehabilitative period in patients after prior critical conditions and reduces the need for invasive hardware methods of correcting endotoxemia and MOD, which determines its economic expediency in addition to therapeutic one. Key words: critical conditions, oxidative stress, the antioxidants Ceruloplasmin and Laprot.